Motor unit number index as an individual biomarker: Reference limits of intra-individual variability over time in healthy subjects. Issue 9 (September 2020) - Delmont, Emilien; Wang, François; Lefaucheur, Jean-Pascal; Puma, Angela; Breniere, Céline; Beaudonnet, Guillemette; Cintas, Pascal; Collin, Romain; Fortanier, Etienne; Grapperon, Aude-Marie; Jomir, Laurent; Kribich, Hafida; et al.
Highlights: Motor unit number index (MUNIX) variation depends on the experience of the operator. A 20% change in MUNIX sum score is significant. MUNIX could be used as a biomarker in the follow-up of neuromuscular disorders. Abstract: Objective: Motor unit number index (MUNIX) is proposed to monitor neuromuscular disorders. Our objective is to determine the intra-individual variability over time of the MUNIX. Methods: In 11 different hospital centres, MUNIX was assessed twice, at least 3 months apart (range 90–360 days), in tibialis anterior (TA), abductor pollicis brevis (APB), abductor digiti minimi (ADM) and deltoid muscles in 118 healthy subjects. MUNIX sum score 2, 3 and 4 were respectively the sum of the MUNIX of the TA and ADM, of the TA, APB and ADM and of the TA, APB, ADM and deltoid muscles. Results: The repeatability of the MUNIX was better for sum scores than for single muscle recordings. The variability of the MUNIX was independent of sex, age, interval between measurements and was lower for experienced than non-experienced operators. The 95th percentile of the coefficient of variability of the MUNIX sum score 2, 3 and 4 were respectively 22%, 18% and 15% for experienced operators. Conclusions: The MUNIX technique must be performed by experienced operators on several muscles to reduce its variability and improve its reliability. Significance: A variation of the MUNIX sum score ≥20% can be interpreted as a significant change of muscle innervation.